DESCRIPTION OF THE MOTIVATION OF HYPERTENSION AND DIABETES MELLITUS PATIENTS IN FOLLOWING PROLANIS ACTIVITIES - Zuliani, Zuliani (Nurse and Holistic Care, 2023)
Background: Prolanis is a health service system to maintain the health of people with chronic diseases. Prolanis will not run well without community participation, while the participation of people with hypertension and diabetes mellitus in participating in Prolanis activities is influenced by motivation. Objective: The purpose of this study was to describe the motivation of people with hypertension and diabetes mellitus in following Prolanis activities at the Nurwachid Inpatient Primary Clinic. Methods: This research design used descriptive. The research was conducted in August 2022 at the Nurwachid Inpatient Primary Clinic. The population in this research is the Prolanis program participants. The sampling technique used total sampling obtained a sample of 45 respondents, consisting of 25 participants diabetes mellitus and 20 participants sufferer hypertension. Motivational instruments with questionnaires, Analysis of statistical test data with univariate. Result: The results showed that more than half of the respondents had good motivation (53.3%), and most of the respondents had good participation (73.3%). Conclusion: It is hoped that Prolanis officers will improve their special services in carrying out Prolanis activities, so that Prolanis participants are motivated which will lead to increased participation in participating in Prolanis activities. Thus, facilitating monitoring and evaluation in providing guidance and health services.